Price Theory and Applications - HIRSHLEIFER, Jack (PRENTICE HALL, 1976)
Featuring extensive coverage of information, uncertainty, and game theory, this volume is a new edition of a classic textbook in intermediate microeconomics. It contains over a hundred examples illustrating the applicability of economic analysis not only to mainline economic topics but also issues in politics, history, biology, the family, and many other areas. The text generally describes recent research published in scholarly books and articles, providing students with a good idea of the scientific work done by professional economists in a variety of areas. Jack Hirshleifer is Distinguished Professor of Economics, Emeritus at the University of California, Los Angeles Amihai Glazer is Professor of Economics at the University of California, Irvine David Hirshleifer holds the Ralph M. Kurtz Chair of Finance at The Ohio State University.